Volume 1: Offshore Technology; Polar and Arctic Sciences and Technology 2011
DOI: 10.1115/omae2011-49038
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Investigation Into the Pull-Out Capacity of Suction Caissons in Sand

Abstract: The pull-out performance of conventional suction caissons (with upright walls) has been previously investigated by a number of researchers. However, less attention has been formerly paid to tapered suction caissons. This paper reports some results from an experimental investigation into the pull-out performance of tapered suction caissons. The 1g experiments have been carried out on eight small scale suction caissons. Four specimens have had upright walls while the other four had a positive wall slope of 10%. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…However, the uplift capacity-displacement curve and the suction-displacement curve exhibited similar shapes in all tests. Analogous changes in uplift resistance and suction during pullout were also observed in experiments with lower displacement rates (see Kakasoltani et al (2011) and Wang et al (2019)). Therefore, it can be concluded that the displacement rate has a small effect on the stress-displacement relationship of the skirted foundation, but significantly affects the magnitude of uplift capacity as well as the magnitude of suction in the skirt compartment.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…However, the uplift capacity-displacement curve and the suction-displacement curve exhibited similar shapes in all tests. Analogous changes in uplift resistance and suction during pullout were also observed in experiments with lower displacement rates (see Kakasoltani et al (2011) and Wang et al (2019)). Therefore, it can be concluded that the displacement rate has a small effect on the stress-displacement relationship of the skirted foundation, but significantly affects the magnitude of uplift capacity as well as the magnitude of suction in the skirt compartment.…”
Section: Resultssupporting
confidence: 67%
“…1. Suction generation between the top plate of the skirted foundation and the soil plug confined by the skirts Kelly et al (2004), Luke et al (2005), Kakasoltani et al (2011), Hung et al (2017), Zhai and Li (2017), and Xie et al (2020).…”
Section: Introductionmentioning
confidence: 99%